Soluble Powdered Natural Dyes from Malaysia - June Ngo, Siok Kheng; Ong, Wan Fen; Fasihuddin Badruddin, Ahmad; Kopli, Bujang (Universiti Malaysia Sarawak, (UNIMAS), 2011)
In recent years, the number of textile craft practitioners in Malaysia using natural dyes in their work has dwindled drastically due to the tedious process of extracting the colours. Some of the plants and fruits used for natural dyeing also are seasonal. Thus, in order to have the natural dyes readily available throughout the year, it has to be converted into powdered form. This paper highlights an on-going research that produces soluble powdered natural dye extracts from the Sebangki bark (Neesia spp., Bomb.; Tristaniopsis spp., Myrt.), Engkerabai Paya leaves (probably Psychotria viridiflora Zollo ex. Miq.) and Engkudu roots (Morinda citrifolia L.). These three natural colourants are typically used by the local native Iban community in Sarawak to dye silk and cotton threads for Pua Kumbu weaving. The two primary objectives of this research are to convert the extract of the natural dyes into soluble powdered form using solvent extraction method and to formulate textile dyeing recipes with good colourfastness and lightfastness using the powdered natural dyes extracts. The results of the experiments have proven that (i) the usage of distilled water and ethanol as solvents to extract the natural dyes from Neesia spp., Bomb.; Tristaniopsis spp., Myrt. bark, Morinda citrifolia L. roots, Psycho tria viridiflora Zollo ex. Miq. leaves and also (ii) the freeze drying method to convert the liquid dye extract into soluble powdered form, have been successfully carried out. Textile dyeing recipes using the soluble powdered extract were also successfully formulated.